What are the emerging features of community health insurance schemes in east Africa? - Robert Basaza; George Pariyo; Bart Criel (Dove Medical Press, 2009)
Robert Basaza1,3, George Pariyo2, Bart Criel31Ministry of Health Uganda, Kampala, Uganda; 2Department of Health Policy, Planning and Management, Makerere University school of Public Health, New Mulago Hospital Complex, Kampala, Uganda; 3Institute of Tropical Medicine Nationalestraat 155, B-2000 Antwerp, BelgiumBackground: The three East African countries of Uganda, Tanzania, and Kenya are characterized by high poverty levels, population growth rates, prevalence of HIV/AIDS, under-funding of the health sector, poor access to quality health care, and small health insurance coverage. Tanzania and Kenya have user-fees whereas Uganda abolished user-fees in public-owned health units.Objective: To provide comparative description of community health insurance (CHI) schemes in three East African countries of Uganda, Tanzania, and Kenya and thereafter provide a basis for future policy research for development of CHI schemes. Methods: An analytical grid of 10 distinctive items pertaining to the nature of CHI schemes was developed so as to have a uniform lens of comparing country situations of CHI. Results and conclusions: The majority of the schemes have been in existence for a relatively short time of less than 10 years and their number remains small. There is need for further research to identify what is the mix and weight of factors that cause people to refrain from joining schemes. Specific issues that could also be addressed in subsequent studies are whether the current schemes provide financial protection, increase access to quality of care and impact on the equity of health services financing and delivery. On the basis of this knowledge, rational policy decisions can be taken. The governments thereafter could consider an option of playing more roles in advocacy, paying for the poorest, and developing an enabling policy and legal framework.Keywords: community health insurance, low enrolment, policy and Africa